MEMBONGKAR MITOS : KEKERASAN FISIK BUKAN SATU-SATUNYA BENTUK KEKERASAN DALAM BERPACARAN - Frieska Putrima Tadung; Teleng, Melkisedek; Frischa Daluwu; Meivi Lestari Putri Takasihaeng; Merri Y Ch M Menaheside; Oktafin Angelia Maneking; Stela Binei; Vinka Dea Samalam; Pramesti Ardita Katiandagho; Nessa Felisha Bowontari (PT. Giat Konseling Nusantara, 2024)
Dating violence is often associated with physical violence, but other forms of violence can also have a significant impact on victims. This article debunks the myth that physical violence is the only form of dating violence, by outlining other forms of violence such as emotional and psychological violence. Thus, a more comprehensive understanding of dating violence is needed to provide appropriate and effective support to victims. This research also highlights the importance of education and prevention of dating violence to create a safer and healthier environment for all individuals.